Situation on Livelihood Capital of Hired Khmer Households for Rice Production under Agricultural Mechanization in Thoi Lai District, can Tho City (Global Journal of Science Frontier Research, 2017)
Agricultural mechanization is always an indispensable process in the modern agriculture. At the same time, the hired labor groups were marginalized. The case of the hired Khmer households in agriculture in Thoi Lai of Can Tho is a typical example for this study. Data of study was collected through interviews of households by Key informants, and group discussion. the interviews of Key Informants (KI), the interviews of the households and the group discussions. This study was analyzed on the livelihood and its outcomes of 101 hired Khmer households for rice production by the quality and quantity methods.
Keywords: modern agriculture; Key Informants; analyzed; quantity methods